Central nervous system receptor activities of some Malaysian plant species - Chung, L.Y.; Goh, S.H.; Imiyabir, Z. (2005)
In this investigation, 185 plant samples representing more than 30 plant families collected from the Malaysian forests were assessed for their ability to inhibit specific radioligand binding to 5HT1a, GABA(B), and dopamine ( D2S) receptors. For this study, 96- well microplate filtration assays were adopted, and the screening parameters including screening window factor ( z factor) and z' factor indicated that the assays adopted were robust and suitable for medium- throughput screening ( MTS). z factor also indicated that data on plant extracts at 10 mu g/ well were more reliable compared to those obtained from 100 mu g/ well. Therefore, only data at 10 mu g/ well in duplicate were used in the determination of actives. In the preliminary screen, 23 plant extracts were found to show activity ( 50 or higher level of inhibition over the mean of all samples for a given plate) in either one or both of the duplicates. Of these, seven were reconfirmed to be active on 5HT1a receptor in the hit confirmation. The active plant extracts were isolated from Popowia odoardoi Diels ( Annonaceae) ( leaf and stem), Artabotrys roseus Boerl. ( Annonaceae) ( bark), Litsea elliptibacea Merr. ( Lauraceae) ( bark), Decaspermum fruticosum Forst. ( Myrtaceae) ( bark), Dyera costulata ( Miq.) Hook. f. ( Apocynaceae) ( leaf), and Irvingia malayana Oliv. ( Simaroubaceae) ( leaf). However, none of the plant extracts tested were active on either GABA(B) or D2S receptors.